Detection of HHV-6 and EBV and Cytokine Levels in Saliva From Children With Seizures: Results of a Multi-Center Cross-Sectional Study - Bartolini, Luca; Piras, Eleonora; Sullivan, Kathryn; Gillen, Sean; Bumbut, Adrian; Lin, Cheng-Te Major; Leibovitch, Emily C.; Graves, Jennifer S.; Waubant, Emmanuelle L.; Chamberlain, James M.; Gaillard, William D.; Jacobson, Steven (Frontiers in Neurology, 2018)
Background and objective: One third of children with epilepsy are refractory to medications. Growing data support a role of common childhood infections with neurotropic viruses and inflammation in epileptogenesis. Our objective was to determine the frequency of Human Herpesvirus-6 (HHV-6) and Epstein-Barr Virus (EBV) infection and cytokine levels in saliva from children with seizures compared to healthy controls and to controls with a febrile illness without seizures. Methods: In this cross-sectional multi-center study, we collected saliva from 115 consecutive children with acute seizures (cases), 51 children with a fever and no seizures or underlying neurological disease (fever controls) and 46 healthy children (healthy controls). Specimens were analyzed by a novel droplet digital PCR for HHV-6 and EBV viral DNA and a bead-based immunoassay for neuroinflammatory cytokines. Results: Cases included febrile seizures (n=30), acute seizures without (n=53) and with fever (n=4) in chronic epilepsy, new onset epilepsy (n=13), febrile status epilepticus (n=3) and first lifetime seizure (n=12). HHV-6 DNA was found in 40% of cases vs. 37% fever controls and 35% healthy controls, with no statistically significant differences. EBV DNA was also detected with no differences in 17% cases, 16% fever controls and 28% healthy controls. IL-8 and IL-1beta were increased in saliva of 32 random samples from cases compared with 30 fever controls: IL-8 cases mean (SD): 1158.07 pg/mL (1427.41); controls 604.92 (754.04); p=0.02. IL-1beta 185.76 (230.57); controls 86.99 (187.39); p=0.0002. IL-1beta level correlated with HHV6 viral load (p=0.007). Conclusion: Increase in inflammatory cytokines may play a role in the onset of acute seizures and saliva could represent an inexpensive and non-invasive method for detection of viral DNA and cytokines.